Vocabulary size, reading motivation, reading attitudes and reading comprehension performance among Filipino college learners of english - Rosalyn Gunobgunob-Mirasol (International Journal of Evaluation and Research in Education (IJERE), 2019)
Reading is an indispensable tool in the academic world. Most, if not all, activities in varied collegiate courses entail the act of reading. There are many contributing factors that affect one’s ability to read and comprehend text materials effectively. Two of the many factors are the reader’s vocabulary size and their reading motivation. This study examined the relationship of the vocabulary size, reading strategies and the reading comprehension performance of college learners in a comprehensive university in the Philippines. A correlational analysis was employed to ascertain the relationship between the scores in the reading comprehension component of the course and the vocabulary levels tests by Nation [1]. The findings of this study hope to provide useful insights into the prediction of college learners’ reading performance and the teaching of vocabulary in the ESL context as well as the integration of learners’ reading motivation in the curriculum.